2013
DOI: 10.1088/0256-307x/30/6/062301
|View full text |Cite
|
Sign up to set email alerts
|

High-Spin Level Scheme of 120 I

Abstract: Excited states in 120 I are investigated utilizing in-beam gamma-ray spectroscopy following the 114 Cd( 11 B,5n) reaction at 70 MeV bombarding energy. A level scheme is constructed with states up to 9 MeV. The levels are classified into several bands and their possible configurations at low spins are discussed briefly. Based on the linking transitions between different bands at higher spins, the excitation energy of the previously reported 𝑇 1/2 = 53 min isomer is ascertained to be 72 keV. Evidence showing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the A β‰ˆ 130 mass region, the iodine isotopes lie on the lower edge of the present chiral island. In 2003, based on the similar energy spectrum, Moon et al [42] suggested the presence of chiral doublet bands in 120 I. In 2013, Li et al extended both the yrast and side bands up to state and , respectively [43].…”
Section: βˆ†I = 1 Ο‡mentioning
confidence: 98%
See 1 more Smart Citation
“…In the A β‰ˆ 130 mass region, the iodine isotopes lie on the lower edge of the present chiral island. In 2003, based on the similar energy spectrum, Moon et al [42] suggested the presence of chiral doublet bands in 120 I. In 2013, Li et al extended both the yrast and side bands up to state and , respectively [43].…”
Section: βˆ†I = 1 Ο‡mentioning
confidence: 98%
“…Recently, according to the experimental properties of doublet bands in Ref. [42], Moon et al [44] discussed the chiral characteristics and doubling of states for the configuration based on the largescale spherical shell model and total Routhian energy surface calculations, and further suggested a chiral-like pair band in 120 I. Therefore, it is necessary to study the rotational mechanism for the occurrence of the chirality in 120 I and extend the boundary of the island of chirality.…”
Section: βˆ†I = 1 Ο‡mentioning
confidence: 99%